How Does Visual Temporal Processing Affect Chinese Character Reading in Children With Dyslexia? From the Perspective of Inhibition - Rong-An Jhuo
Given that inhibition interacts with visual temporal processing (VTP), the past evidence regarding the influence of VTP on the Chinese character reading of children with dyslexia may not disclose the whole picture without considering inhibition. Thus, the present study is among the first to investigate VTP and cognitive inhibition as well as their relationships to Chinese character reading. We compared the performances of 62 Chinese-speaking children with dyslexia in primary school (n = 62, Mage = 11.36 years) on VTP and inhibition tasks to those in a chronological-age-matched group (CA; n = 62, Mage = 11.57 years) and reading-level-matched group (RL; n = 62, Mage = 8.98 years). The results revealed that children with dyslexia performed worse than both the CA-matched and RL-matched groups in VTP and inhibition after controlling for age, nonverbal intelligence, and attention. Moreover, the relationship between VTP and Chinese character reading was moderated by inhibition in children with dyslexia. VTP is positively related to Chinese character reading, but this relationship is observed only at higher levels of inhibition. Our results suggest that inhibition plays a potential role in VTP and Chinese character reading, especially for those with dyslexia whose proficiency in inhibition is not as intact as that of typically developing children.